Penerapan Media Pembelajaran Papan Pintar Dalam Pembelajaran Matematika Kelas Dua Uptd Sdn 1 Juntinyuat - Syifaun Nafisah; Yayang Furi Furnamasari (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2023)
The application of learning media is needed for problem solving in the form of questions that aim to get the correct answer. Based on the results of interviews and observations, there are several students who have not been able to solve math problems. This study aims to explain the application of smart board media on multiplication and division materials in class II. This research method is Research and Development (R & D), this research method is used to produce a certain product and test the effectiveness of the product. from the diagram results and learner responses, this smart board is very feasible to use as a learning medium that can help in the learning process.